Implementación de técnica de Machine Learning para ubicación de fallas en sistemas de potencia (2017)
"Fault location algorithms are classified into four main categories: one-ended techniques, two terminal methods, traveling-wave techniques and time-tagged methods. Algorithms that belong to the first one are usually based on impedance calculations and, consequently, are affected by diverse error sources such as fault impedance, inaccurate fault type identification, line compensation, line parameters uncertainty, among others. Moreover, increasing algorithms precision may decrease the fault correction time and, therefore, implies positive economic outcomes".-- Tomado del Formato de Documento de Grado.